ANALISIS KESIAPAN PERENCANAAN LAYANAN PENDIDIKAN INKLUSIF PADA KURIKULUM MERDEKA DI SMP ISLAM AL-IKHLAS - Yayat Prihatna; Ilham Alva Ridho; Ahmad Ali Rafi; Khodijah Khodijah (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study aims to analyze the readiness of inclusive education service planning under the Independent Curriculum at Al Ikhlas Islamic Junior High School. The study used a qualitative case study approach, using observation techniques, in-depth interviews, and documentation studies of school leaders, teachers, and learning planning documents. The results indicate that the school has a normative initial commitment to inclusive education, reflected in its vision and mission and acceptance of students with special needs. However, operational policies and SOPs for inclusive services have not been developed in detail. Curriculum and learning planning already refer to the Independent Curriculum through the development of Learning Outcomes, Learning Objective Flows, teaching modules, and the Pancasila Student Profile Strengthening Project. However, the integration of inclusive principles, including the development of Individual Learning Programs, learning differentiation, adaptive assessment, and the use of accessible teaching materials and media, remains limited. From a human resources perspective, teachers demonstrate a positive commitment and have participated in Independent Curriculum training, but specific competencies for inclusive education are still low, and the school does not yet have a dedicated assistant teacher. Learning infrastructure is generally adequate, but disability-friendly facilities and support services (special counseling, collaboration with psychologists/therapists, and structured partnerships with parents) are suboptimal.